DIEP flap customization using Fluobeam® indocyanine green tissue perfusion assessment with large previous abdominal scar. (June 2017) - Fallucco, Michael A.; Snell, Colin P.; Desai, Ankit R.
Abstract: The Fluobeam ® is a portable, near-infrared camera that is held and controlled by the surgeon to visualize tissue perfusion using indocyanine green (ICG) fluorescence imaging. This case report describes how data obtained from ICG imaging allows intraoperative customization in a previously surgically scarred abdomen during autologous Deep Inferior Epigastric Artery Perforator (DIEP) flap bilateral breast reconstruction. The outcome was successful breast mound recreation without fat necrosis.